2020
DOI: 10.1111/his.14006
|View full text |Cite
|
Sign up to set email alerts
|

Tumour budding/T cell infiltrates in colorectal cancer: proposal of a novel combined score

Abstract: Aims The tumour–node–metastasis classification system is used for prognostication purposes and to guide patient management. However, in colorectal cancer (CRC), additional markers are needed to stratify prognostic subgroups. Two promising markers have emerged from large bodies of research: tumour budding and T cell host response (CD3, CD8 and CD45RO infiltrates). However, attempts to combine these two parameters have been sparse. The aim of this study was to perform an assessment of potential protagonists that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
(88 reference statements)
0
23
0
Order By: Relevance
“…The Immunoscore Consortium underlines the significant impact of CD8 + T cells within the densest areas in the tumour centre and at the invasion front, focusing upon stages II and III colon cancers only 24 . Previous work from our group and others show that an attacker–defender combined analysis, namely of tumour budding on one hand and CD8 + on the other hand, can modulate survival times and improve the stratification of patients into better or worse prognostic groups 1,6 . Here, we show that low‐grade tumour budding outweighs the importance of CD8 + T cell presence for overall survival but, in contrast, CD8 + T cell counts have a major impact on patient stratification in the high‐grade budding setting.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The Immunoscore Consortium underlines the significant impact of CD8 + T cells within the densest areas in the tumour centre and at the invasion front, focusing upon stages II and III colon cancers only 24 . Previous work from our group and others show that an attacker–defender combined analysis, namely of tumour budding on one hand and CD8 + on the other hand, can modulate survival times and improve the stratification of patients into better or worse prognostic groups 1,6 . Here, we show that low‐grade tumour budding outweighs the importance of CD8 + T cell presence for overall survival but, in contrast, CD8 + T cell counts have a major impact on patient stratification in the high‐grade budding setting.…”
Section: Discussionmentioning
confidence: 54%
“…investigated budding heterogeneity in multiple blocks/case and found similar results; namely, that heterogeneity in budding counts on cytokeratin staining were low 25 . Secondly, we performed digital image analysis of CD8 + T cell counts, using existing in‐house algorithms 6 . This analysis spared us the extremely laborious task of lymphocyte counting, leading to more precise estimates per case.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Accumulating evidence suggests that adaptive immune response, represented by cytotoxic T cells, plays a crucial role in suppressing tumour invasion and metastasis [6] , and a high density of tumour infiltrating cytotoxic T cells is associated with favourable prognosis in colorectal cancer [7] . A few studies have shown that anti-tumour immune response might restrict tumour budding and indicated that a combined budding-immune cell score might be a stronger predictor of survival than either parameter alone [ 6 , 8 , 9 ]. However, the interplay between anti-tumour immunity and tumour budding/PDCs in the colorectal cancer microenvironment has not been adequately elucidated in terms of specific T-cell subsets driving the associations, as well as tumour molecular features such as microsatellite instability (MSI) status, CpG island methylator phenotype (CIMP) status, long-interspersed nucleotide element-1 (LINE-1) methylation, CTNNB1 (catenin beta 1) and CDH1 (cadherin 1, E-cadherin) expression, and KRAS, BRAF , and PIK3CA mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in the literature draw attention to the association of high tumor budding scores with aggressive tumor characteristics such as advanced pT, pN, AJCC stage, lymphovascular and perineural invasion, distant metastasis, and local tumor recurrence [10,18,[21][22][23][24][25][26]]. Budding's relationship with the histological grade of the tumor is still unclear.…”
Section: Discussionmentioning
confidence: 99%